Study Corrosion Behavior of Alumina Particulate / (AA6061) Aluminum Metal Matrix Composite In Marine Environment - Abdulkader, Niveen J.; Ahmed, Payman Sahbah; Jabar, Mohammed Mahdy (Sulaimani Journal for Engineering Sciences, 2016)
In the present investigation, the static electrochemical corrosion behaviour of (AA6061) Al/Al2O3 composites in Marine (3.5% NaCl) Environment solution was evaluated. The composites were fabricated using liquid metallurgy. The effect of weight percentage (3%, 6%, 9% & 12%) on the corrosion behaviour of composites was investigated. The corrosion rates of composites were calculated using electrochemical method. The results showed that Al/Al2O3 composites have lower corrosion resistance than (AA6061) Aluminium. The corrosion rate was increased by increasing of weight percentage of the alumina particles. Optical microscope were carried out to identify the corroded surface
Keywords: (AA6061) Aluminium alloy; alumina (Al2O3)particles; potentiostatic measurements; Marine (3.5% NaCl) Environment; liquid metallurgy; Corrosion rate